A regional input-output model of the Covid-19 crisis in Italy: Decomposing demand and supply factors - Severin Reissl; Alessandro Caiani; Francesco Lamperti; Tommaso Ferraresi; Leonardo Ghezzi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2022)
We extend the regional input-output model for the economic impact assessment of Covid-19 lockdowns in Italy proposed in Reissl et al. (2021) by incorporating the effects of changes in mobility on the level and composition of consumption demand. We estimate the model on sectoral data for 2020 and perform an out-of-sample validation exercise for the first half of 2021, finding that the model performs well. We then evaluate the relative importance of demand- and supply-side factors in determining our simulation results. During the national lockdown of spring 2020 the impacts of supply-side (labor) shocks can account for the vast majority of output losses. In the following stages of the epidemic income and mobility-related effects on final demand play pivotal roles at the aggregate and regional levels, as well as for most sectors. While policies supporting demand may hence be appropriate, their effectiveness may be hampered when demand is chiefly restrained by the mobility-related effect, and not by income.
Keywords: C63; C67; D57; E17; I18; R15; 330; Input-output; Covid-19; Lockdown; Italy; Demand and Supply Shocks